Correlations Between Master Adaptive Learners’ Characteristics and Anatomy Performance in an Active and Gamebased Anatomy Learning - Asty Amalia Nurhadi; Budu; Andi Alfian Zainuddin; Ichlas Nanang Afandi; Haerani Rasyid; Irawan Yusuf; Irfan Idris; Indang Ariati Arifin; Lelimiska Irmadani Syarif; Gita Vita Soraya (Education in Medicine Journal, 2026)
Master Adaptive Learners (MALs) can adjust their learning strategies to overcome challenges, a key trait for success in complex subjects like anatomy. This study explored the correlation between MAL characteristics—curiosity, motivation, growth mindset, and resilience—and anatomy performance in an active, game-based learning environment. A cross-sectional study was conducted among 246 first-year medical students at Hasanuddin University in 2022. The anatomy course used blended, active learning, and game-based learning methods. MAL traits were measured using validated Indonesian language instruments: the Curiosity and Exploration Inventory-II, Academic Motivation Scale short form, Growth Mindset Scale, and Connor-Davidson Resilience Scale. Anatomy performance was assessed through a comprehensive final exam. Non-parametric Spearman’s rank correlation was applied due to non-normal data distribution. Students achieved a high average score (mean = 76.7, standard deviation (SD) = 16.2). Most MAL traits showed no significant correlation with performance: curiosity, motivation, and resilience (p > 0.05). However, growth mindset demonstrated a weak but significant positive correlation (r = 0.26, p < 0.001). In conclusion, while active learning may support student success regardless of MAL traits, the growth mindset was modestly linked to better performance. Curriculum strategies that cultivate a growth mindset may enhance learning outcomes in anatomy education.